Ohlson's model as a tool to predict performance: a comparative study between commercial bank of ceylon plc and banking industry - Niresh, J.A.; Balaputhiran, S. (Sri Lankan Journal of Banking and Finance, 2022)
The Banking Industry provides a substantial contribution to the Sri Lankan economy. This research aims to compare the forecast performance indicators of the Commercial Bank of Ceylon PLC with the Banking industry. The researcher has selected the Commercial Bank of Ceylon PLC as a sample since it is ranked 1st in the Banking Sector on Colombo Stock Exchange and the only Sri Lankan bank to be ranked for the 10th consecutive year by "The Banker". In this study, the researcher has used statistical software named R to analyze the data considering Profitability, Liquidity, and Capital Adequacy indicators. Data has been gathered over ten years from 2009 to 2018, and the predictions were made adopting Ohlson's Forecasting Model for the subsequent years 2019 and 2020. The Commercial Bank PLC is on track with the industry norms except in areas, especially Net Interest Margin, Liquidity, and Core Capital Ratio, where significant improvements are needed to bring their performance on track, the findings reveal. The Ohlson model's robustness was tested using Mean Absolute Percentage Error (MAPE). It confirms that the model best fits the two variables used in the study named Core Capital Ratio and Total Capital Ratio.
Keywords: Financial performance; Banking Industry; Profitability; Liquidity; Capital Adequacy